Public health aspects of feral deer, goats and pigs in New Zealand: A review to inform eradication decisions. (December 2015) - Wilson, Nick; Blaschke, Paul; Thomson, George; Nghiem, Nhung; Horrocks, John
Abstract: The research described in this paper sought to review the public health issues arising from the presence of feral deer, goats and pigs in New Zealand. Key findings were that while recreational hunting of these animals is likely to provide physical and mental health benefits, and contribute to food security, likely health‐related harms from these animals include (i) injury risks from the associated firearms used in hunting; (ii) as reservoirs for zoonotic diseases; (iii) reduced mental health benefits of wilderness experience and natural ecosystems; and (iv) likely contribution to flooding risk via forest damage. Further research could better quantify these issues.